O ensino por competências: uma visão das Instruções Reguladoras do Ensino por Competências e suas decorrências para as práticas educativas no Centro de Preparação de Oficiais da Reserva de Porto Alegre (CPOR/PA) - Regus, Carlos Guilherme Maciel (2015)
The research, primarily on documentary evidence, is analytical focus this vision in the Instructions Regulatory Teaching Skills in Officer Training Center of Porto Alegre Reserve (CPOR / PA) on teaching competency, identifying consequences of this vision for practices this educational institution. The study is in line with the research developed in the Research Field Teacher Training, theories and educational practices of the Program of Postgraduate Education (Master of Education) La Salle University Center. The documentary analysis of the Regulatory Instructions in CPOR / PA combined with a dialogue established with authors discussing the teaching of skills is investigative research corpus. Thus, the theoretical framework underlying the study will be structured in this discursive-analytic movement in that cross different views: the researcher, the authors identified and that the Instructions Regulatory. Based on this framework and the findings arising from the research will be selected from the content analysis technique, some themes concerning the derivations of views on teaching competency for educational practices in CPOR / PA. Among the main findings of the study include: the learning content should not be reduced only to subjects; that the school curriculum should emphasize the importance of cognitive activity of thinking; physical and motor skills that are important to be developed by the school seeking to meet the principles of good health; that moral capabilities are important to be developed in the school environment, but everyone (school, family and society) has a predominant role in its development; that the functional maps, professional profiles, curriculum vitae of people from various fields, job offers (minimum requirements), etc., are described all the skills and expertise you want from a professional (for the teacher is no different) ; to teach attitudes and values is possible, but it's more important to show them; it's possible the inclusion of skills in higher education; the evaluation in a teaching model for skills is not easy, but it can be well regulated; that within a teaching model for technical skills fit teachers, reflective and critical, according to the selected theme; that the option of adopting a teaching model for skills can also be described as a pedagogical innovation. These findings may identify areas for implementation of these instructions Regulatory so that such implementation makes possible the improvement and qualification of educational practices.